2018
DOI: 10.1002/adfm.201805825
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Roll‐to‐Roll Produced Fullerene‐Free Organic Photovoltaic Devices via Temperature‐Controlled Slot Die Coating

Abstract: Solution‐processed organic photovoltaics (OPVs) have continued to show their potential as a low‐cost power generation technology; however, there has been a significant gap between device efficiencies fabricated with lab‐scale techniques—i.e., spin coating—and scalable deposition methods. Herein, temperature‐controlled slot die deposition is developed for the photoactive layer of OPVs. The influence of solution and substrate temperatures on photoactive films and their effects on power conversion efficiency (PCE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
66
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 65 publications
1
66
0
Order By: Relevance
“…[31][32][33][34][35] For example, Yan and co-workers showed that blade-coated PSCs with PffBT4T-2OD:PC 71 BM based BHJ can produce a high PCE of up to 9.9%. [37][38][39] However, the slot-die method has not been well studied and the efficiency of slot-die based devices has still remained low, compared to the high PSCs in the recent reported spin-coating based PSCs. [31] In particular, 12.88% PCE was achieved in doctor blade-coated PBDB-TF:IT-4F PSCs through controlling the surface morphology of the ZnO interlayer; [36] and more recently, Hou and co-workers demonstrated a top efficiency of 13.1% from the blade-coated PSCs based on T1:IT-4F.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…[31][32][33][34][35] For example, Yan and co-workers showed that blade-coated PSCs with PffBT4T-2OD:PC 71 BM based BHJ can produce a high PCE of up to 9.9%. [37][38][39] However, the slot-die method has not been well studied and the efficiency of slot-die based devices has still remained low, compared to the high PSCs in the recent reported spin-coating based PSCs. [31] In particular, 12.88% PCE was achieved in doctor blade-coated PBDB-TF:IT-4F PSCs through controlling the surface morphology of the ZnO interlayer; [36] and more recently, Hou and co-workers demonstrated a top efficiency of 13.1% from the blade-coated PSCs based on T1:IT-4F.…”
mentioning
confidence: 99%
“…[35] Hou and coworkers also presented the excellent PCE of 9.5% in doctor blade-coated PSCs based on PTB7-Th and 3,9-bis(2-methylene-(3-(1,1-dicyanomethylene)-indanone))-5,5,11,11-tetrakis(4hexylphenyl)-dithieno[2,3-d:2′,3′-d′]-s-indaceno[1,2-b:5,6-b′] dithiophene) (ITIC) NFA. [39,40] Furthermore, the PCEs of roll-to-roll slot-die PSCs have been only within ≈(5-7)% [39][40][41] and the 7.32% PCE has been known as the top record efficiency of the roll-to-roll processed PSC. [21] Although the abovementioned studies showed promising results, the blade coating method could have limited practicality in manufacturing, especially for roll-to-roll production, due to the method having difficulty in controlling film-thickness and fabricating stripe patterns; and in fact, there has been no report on the roll-to-roll fabrication of blade-coated PSCs.…”
mentioning
confidence: 99%
See 3 more Smart Citations